2013
DOI: 10.1177/0194599812472864
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pneumococcal Polysaccharide Vaccine in a Mouse Model of Allergic Rhinitis

Abstract: These results suggest that PPV administered before or after sensitization suppresses Th2 response and enhanced induction of regulatory T cells in an allergic rhinitis model. In addition, there was no significant difference between the degrees of effects in these 2 conditions. In the future, we can consider PPV to be a preventative agent for allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
3
7
0
1
Order By: Relevance
“…The present study demonstrated that intranasal pretreatment with PC suppresses nasal symptoms and allergic inflammation of the nasal mucosa in a murine model of AR. The inhibitory effects of intranasal immunization with PC on nasal symptoms are similar to those reported by previous studies, in which nasal symptoms in a murine AR model induced by sensitization with Der f were reduced by intranasal pretreatment with pneumococcal polysaccharide vaccine and pneumococcal conjugate vaccine . Furthermore, in the present study, the levels of serum IgE and eosinophil infiltration into the nasal mucosa were significantly decreased by intranasal PC pretreatment similar to the experiments using pneumococcal vaccines .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The present study demonstrated that intranasal pretreatment with PC suppresses nasal symptoms and allergic inflammation of the nasal mucosa in a murine model of AR. The inhibitory effects of intranasal immunization with PC on nasal symptoms are similar to those reported by previous studies, in which nasal symptoms in a murine AR model induced by sensitization with Der f were reduced by intranasal pretreatment with pneumococcal polysaccharide vaccine and pneumococcal conjugate vaccine . Furthermore, in the present study, the levels of serum IgE and eosinophil infiltration into the nasal mucosa were significantly decreased by intranasal PC pretreatment similar to the experiments using pneumococcal vaccines .…”
Section: Discussionsupporting
confidence: 90%
“…The same results were observed in the experiments using pneumococcal vaccines, although the administration of killed Spn before OVA sensitization significantly enhanced IFN‐γ production from mediastinal lymph node T cells . Furthermore, it has been reported that regulatory T cells are associated with the suppression of Th2‐type immune response by pneumococcal vaccines . Although PC is a T cell‐independent antigen and does not induce regulatory T cells, conjugation to a protein carrier such as KLH allows the involvement of T cells, indicating that intranasal administration of PC‐KLH might have induced regulatory T cells and suppressed IL‐4 production.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Children with pre-existing neurologic conditions and immune compromise were at increased risk of pH1N1-associated death after PICU admission 39. Most of the available safety data indicated that the single-dose use of peramivir in adults and pediatric outpatient populations commonly led to AEs that reportedly included diarrhea, nausea, vomiting, and neutropenia 12,61,62. Available data related to AEs of multiple-dose peramivir in critically ill patients are scarce 37…”
Section: Resultsmentioning
confidence: 99%